2009
DOI: 10.1126/scisignal.2000143
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Increases Vascular Senescence and Susceptibility to Ischemic Injury Through Chronic Activation of Akt and mTOR

Abstract: Obesity and age are important risk factors for cardiovascular disease. However, the signaling mechanism linking obesity with age-related vascular senescence is unknown. Here we show that mice fed a high-fat diet show increased vascular senescence and vascular dysfunction compared to mice fed standard chow and are more prone to peripheral and cerebral ischemia. All of these changes involve long-term activation of the protein kinase Akt. In contrast, mice with diet-induced obesity that lack Akt1 are resistant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
113
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 54 publications
(93 reference statements)
8
113
1
3
Order By: Relevance
“…17 It was recently demonstrated [18][19][20] that chronic reduction of mammalian target-of-rapamycin (mTOR) signaling by rapamycin extends lifespan in mice by delaying aging. 19 Consistent with this observations, inhibition of mTOR delays EC senescence in vivo 21 and in vitro, 22 improves vascular outcomes of stroke, 23,24 and has been shown to have EC-dependent vasodilatory effects. 25,26 Although distal EC dysfunction has been observed with rapamycin-eluting stents implanted in coronary heart disease patients, 27,28 recent studies have shown that this effect may be due to delayed or absent re-endothelization of the stent, 29 or to effects of the stent itself.…”
Section: Introductionsupporting
confidence: 59%
“…17 It was recently demonstrated [18][19][20] that chronic reduction of mammalian target-of-rapamycin (mTOR) signaling by rapamycin extends lifespan in mice by delaying aging. 19 Consistent with this observations, inhibition of mTOR delays EC senescence in vivo 21 and in vitro, 22 improves vascular outcomes of stroke, 23,24 and has been shown to have EC-dependent vasodilatory effects. 25,26 Although distal EC dysfunction has been observed with rapamycin-eluting stents implanted in coronary heart disease patients, 27,28 recent studies have shown that this effect may be due to delayed or absent re-endothelization of the stent, 29 or to effects of the stent itself.…”
Section: Introductionsupporting
confidence: 59%
“…47 It is noteworthy that a diet high in fats and refined sugars (HFS) did not exacerbate histopathological damage or behavioral impairments as previously reported in focal ischemia models. 10,11 Although it is possible that a HFS diet does not have an effect on pathologic or behavioral injury in the present 2-VO model, other explanations for this lack of effect exist. For example, it has been (A) Animals exposed to 2-vessel occlusion (2-VO) plus the physical and cognitive activity (PA/CA) rehabilitation paradigm displayed significantly shorter latencies to locate the hidden platform during the acquisition trials indicating superior learning abilities compared with 2-VO animals that did not receive rehabilitation at PSW 16 (*Po0.01).…”
Section: Discussionmentioning
confidence: 68%
“…3 However, other modifiable lifestyle choices may significantly influence vascular health as well. For example, high-fat diets accelerate vascular senescence 10 and exacerbate ischemic stroke damage when exposure extends from the early post-weaning period. 11 Preclinical studies often overlook the importance of modeling co-morbid conditions (e.g., old age, unhealthy diet) when assessing intervention efficacy 12 and this failure to reflect key aspects of the clinical setting undoubtedly contributes to the so-called translational roadblock.…”
Section: Introductionmentioning
confidence: 99%
“…In general, mTORC1 is rapamycin-sensitive, and mTORC2 is rapamycin-insensitive. Within the mTORC1 and mTORC2 complexes, mTOR is resistant to acute rapamycin treatment, but prolonged exposure to rapamycin can block the assembly of mTORC2 components (1) and Akt activation (2). In recent studies focused on ischemic disease, the role of signaling pathways has not been identified clearly (2,3).…”
Section: Introductionmentioning
confidence: 99%